EIN LOGOS FÜR DAS SEIN UND DEN GOTT. HEIDEGGERS AUSEINANDERSETZUNG MIT DER THEOLOGIE AB DEN DREISSIGER JAHREN II - MARAFIOTI, Rosa Maria (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
A Logos for Being and God. Heidegger’s Confrontation with Theology from the 1930s. II. Heidegger’s entire itinerary is characterised by the search for a living relationship with God, and thus for a Logos able to think and name the divine without objectifying its divinity. Getting into a dialogue with Western philosophers and theologians and distinguishing the fields of thinking, faith and science one from the other, since the 1930’s Heidegger claims that, if the traditional theology has seen God as the supreme being, metaphysics, on its part, has identified it with Being as such. According to Heidegger, the onto-theo-logical constitution of metaphysics has developed itself by means of the reception of the Jewish-Christian concept of an almighty God as creator. This process has led to the fulfilment of the machination in the totalitarian regimes of the 20th century. Heidegger speaks about the poverty of thought and about the consequent impossibility of building an ontology as well as a theology. Nevertheless, he still waits for the hint of a last God, in so far as he assumes that a renewed manifestation of the divine must be prepared through the overcoming of the forgetfulness of Being and God.